Including citizens through co-design in a participatory research project to explore innovative agro-food systems: the case of future dairy livestock systems - Coeugnet, Philippine; Labatut, Julie; Duval, Julie; Vourc'h, Gwenaël (Frontiers in Sustainable Food Systems, 2023)
Livestock farming and its negative impacts are increasingly singled out by society, its evolution towards more sustainable systems is therefore a key aspect of the transition of agro-food systems. It is necessary to rethink livestock systems’ research and innovation processes and develop innovative solutions. Including citizens, non-professionals of the sector, who are less influenced by the current organization of the agricultural sector could be an opportunity to generate innovative solutions but they have been kept away from research and innovation processes so far. In this context, we implemented a co-design process involving researchers, livestock professionals and citizens in a participatory research project aiming at producing knowledge and developing innovative solutions for the future mountain dairy systems. For this, we have adapted the KCP design method known to promote the exploration of innovative solutions, support the agro-ecological transition and build a common horizon. The analysis of this collective dynamic and its outputs allowed us to highlight the positive contribution of citizens during the design process, even if (and maybe even more) they are not livestock experts. The citizens participated in the formulation of new knowledge by questioning the researchers and livestock professionals and were less influenced by the current system. This contributed to the exploration of original and varied solutions for livestock farming systems. This experimentation offers perspectives for including citizens into agro-food systems research and innovation process. It also opens up interesting perspectives for the fields of citizen science and co-design research.